Hubungan Kondisi Fasilitas Pedestrian Terhadap Aspek Keselamatan Pejalan Kaki Di Depan Lippo Plaza Kota Kendari - Sarmin, La Ode; Magribi, La Ode Muh; Sunaryo, Sunaryo (Universitas Sulawesi Tenggara, 2020)
This study aims to determine the characteristics of pedestrians, the existing conditions of pedestrian facilities, aspects of pedestrian safety, and the relationship of conditions of pedestrian facilities to aspects of pedestrian safety in front of the Lippo Plaza Kendari City. Technical data analysis using mathematical equations and non parametric statistical analysis with the help of SPSS 21.The results showed that the characteristics of the foot in front of the Lippo Plaza Kendari Cityfrom the calculation results obtained by the pedestrian flow (Q) in segment 1 at 16:00 to 21:00 at 1,61 people/meter/minute while in segment 2 at 1,56 people/meter/minute, the average speed of the pedestrian room (Vs) is 61,35 meters/minute, pedestrian density (D) is 0,026 people/meter, pedestrian space (S) is 38,72 meters2/person. The existing condition of the pedestrian facility in front of the Lippo Plaza Kendari City was included in the criteria that is not good that is equal to 39,3% while the safety aspects included in the criteria are not good at 46%. There is a relationship between the condition of pedestrian facilities and aspects of pedestrian safety but is very weak with a value of 0,139